International Standards regarding the Right to Identity under the Convention on the Rights of the Child and the Protection of Intersex Children against Forced and Coercive Surgical Treatments - Cruz Espinoza, Peter Alexis (2023)
Domestic laws and policies around the world remain reluctant to fully guarantee intersex children’s human rights during forced and coercive surgeries performed on their bodies. The right to identity has evolved as a human right but has not been the main academic concern regarding these practices. Therefore, the present study first establishes the issues involved with forced and coercive surgical interventions on intersex children based on an intersectional and gender-based approach. Then, the evolution of the right to identity is presented through international human rights instruments as well as its link to other human rights related to the central problematic of the study. Lastly, based on international obligations regarding the child’s right to identity (Article 8 of the Convention on the Rights of the Child), several new international standards emerge from the production of the Committee on the Rights of the Child as the treaty body. The Committee on the Rights of the Child has shown a dynamic, expansive, and progressive interpretation of the child’s right to identity. Nonetheless, this has been not concretely focused on the intersex children and has limitations based on its non-binding nature. With these results, this study aims to contribute to the academic discussion on children’s human rights involved in these often-overlooked issues.